Development and validation of an instrument to assess attacking tactical behavior in football - Dahlan, Firmansyah; Hamzah, Fajri; Sihombing, Binsar Hasudungan; Burhan, Ahmad Syarif; Junaidi (Journal Sport Area, 2025)
Background: Existing tactical assessment tools generally evaluate overarching game principles but lack positional specificity and do not integrate decision-making and execution within a coherent framework. Moreover, these instruments were developed outside the Indonesian context, creating a clear gap for a position-integrated tool tailored to the tactical demands of youth football in Indonesia. Objectives: Thusstudy aimed to develop and validate a new instrument for assessing attacking tactical behavior in youth football by incorporating positional roles and experience-level differences. Methods: The instrument was developed through content validation with seven experts using Aiken’s V. Construct validity was subsequently assessed via the known-groups method, involving 72 football players from a university club and youth teams. The instrument’s reliability was further evaluated through inter-rater reliability with three raters and test–retest reliability with 36 youth football players. Finding/Results: The instrument demonstrated excellent content validity (Aiken’s V = 0.952) and good discriminant validity, with college players scoring significantly higher than youth players. Reliability analyses indicated strong inter-rater (ICC = 0.837-0.939) and test–retest reliability (ICC = 0.801-0.923). Compared with other instruments, the tool offers greater positional detail and holistic integration of tactical behavior, enabling more context-specific evaluation of attacking actions. Conclusion: The instrument was found to be valid and reliable for assessing attacking tactics in youth football. Although the sample size was limited and the instrument development did not yet address defensive and transitional phases, these findings support further refinement and application in future research.